Analisis Penggunaan Bahasa Gaul Pada Media Sosial Tiktok - Sholihah, Wahyuni; Sholikah, Syayidatus; Sholihah , Wahyuni (Signifiѐ, 2024)
Language is a bridge of communication between individuals and groups, which plays an important role in creating harmony. In everyday life, casual language or slang is more effective than formal language because it is light and easy to understand. The digital era reinforces the use of slang, especially through social media such as TikTok, which is a virtual interaction space. On TikTok, slang often appears in posts and comments, such as “fyp,” “kane,” or “gtw.” These terms reflect the times and technology, although they are sometimes difficult to understand for those less familiar with social media.